Imidazolium-Based Acid Catalysts for Deacetylation and Debenzoylation - Ho, Wen-Yueh; Pantawane, Amit; Tsai, Qiao; Yang, Meng-Jie; Yen, Sheng-Chieh; Chen, Jyun-Siao; Reddy, Julakanti Satyanarayana; Wu, Hsin-Ru; Luo, Shun-Yuan (Synthesis, 2025)
Herein, we report a simple and efficient protocol for the deprotection of acetate and benzoate to alcohols, catalyzed by an imidazolium-based acid. Acetate groups were selectively removed while benzoate groups remained intact under mild conditions, and benzoate needed harsher conditions. Notably, this protocol was successfully employed for carbohydrate-building block synthesis in a one-pot strategy, was compatible with different ester protecting groups such as O-Bz, O-Ts, and O-Piv and site-selective deprotection of acetate. The reusable, environmentally benign catalyst enabled smooth operation, resulting in a promising protocol for deprotection.
Keywords: Deacetylation; Imidazolium catalyst; Acid catalyst; Debenzoylation; Reuse of catalyst